Efficient Mercury Capture Using Functionalized Porous Organic Polymer. Issue 31 (14th June 2017) - Aguila, Briana; Sun, Qi; Perman, Jason A.; Earl, Lyndsey D.; Abney, Carter W.; Elzein, Radwan; Schlaf, Rudy; Ma, Shengqian
Abstract : The primary challenge in materials design and synthesis is achieving the balance between performance and economy for real‐world application. This issue is addressed by creating a thiol functionalized porous organic polymer (POP) using simple free radical polymerization techniques to prepare a cost‐effective material with a high density of chelating sites designed for mercury capture and therefore environmental remediation. The resulting POP is able to remove aqueous and airborne mercury with uptake capacities of 1216 and 630 mg g −1, respectively. The material demonstrates rapid kinetics, capable of dropping the mercury concentration from 5 ppm to 1 ppb, lower than the US Environmental Protection Agency's drinking water limit (2 ppb), within 10 min. Furthermore, the material has the added benefits of recyclability, stability in a broad pH range, and selectivity for toxic metals. These results are attributed to the material's physical properties, which include hierarchical porosity, a high density of chelating sites, and the material's robustness, which improve the thiol availability to bind with mercury as determined by X‐ray photoelectron spectroscopy and X‐ray absorption fine structure studies. The work provides promising results for POPs as an economical material for multiple environmental remediation applications. Abstract : Porous organic polymers (POPs) are a promising class of materials for various environmental remediation purposes. The thiol functionalized POP, POP‐SH, is shown to rapidly remove the toxic metal mercury from aqueous solutions and through vapor adsorption with uptake capacities of 1216 and 630 mg g −1, respectively. The material has promising real‐world applications due to its stability, selectivity, and reusability.